PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN MERUMUSKAN SOLUSI INOVATIF ISU SDA LOKAL PADA SISWA SEKOLAH DASAR - Sri Wahyuni; Erni Suharini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the necessity to enhance students' skills in problem-solving and formulating innovative solutions for local natural resource (SDA) issues, which are fundamental to environmental citizenship. Initial observations indicated that while students possess basic knowledge of SDA (air, soil, plants, animals), their understanding and application of sustainable management, analysis of exploitation impacts, and proposal of creative solutions were still diverse and needed improvement. This research aims to investigate the influence of the Project-Based Learning (PjBL) model on the ability of fifth-grade students to formulate creative and innovative solutions for local SDA problems. The study employed a Quasi-Experimental design with a sample of fifth-grade students from SD Negeri Gayamsari 02. The PjBL model was implemented through a project titled